Short and long-term costs among women experiencing preterm labour or preterm birth: the German experience - Shibani Pokras; Jeanne Pimenta; Evie Merinopoulou; Dimitra Lambrelli (BMC, 2018)
Abstract Background Preterm labour and birth (PTL/PTB) is characterised by major health and developmental risks for children, life-changing consequences for their families, and substantial healthcare and economic challenges for wider society. While it is known that PTL/PTB impacts infant healthcare costs in the short and long term in Germany, maternal costs have not been described in detail. The aim of this study was to comprehensively describe costs and resource use among PTL/PTB mothers during pregnancy, at hospitalisation for delivery, and up to three years after delivery-overall and according to gestational age (GA) at delivery. Methods This study used data from the Statutory Health Insurance (SHI) sample of the AOK Hessen database in Germany. Mothers aged 12-44 years with deliveries between 2009 and 2013 and > 9 months of medical history prior to delivery were included. PTL/PTB mothers were defined by an International Classification of Diseases, 10th Revision (ICD-10) code for PTL during pregnancy, a diagnosis-related group (DRG) code indicating birthweight < 2500 g, or delivery of an infant < 37 weeks GA. Inpatient and outpatient resource use and total direct medical costs were examined during pregnancy, at delivery hospitalisation, and up to three years post-delivery. Results Of all mothers, 2147 (20%) experienced PTL/PTB. During pregnancy, median costs for PTL/PTB mothers were €2130. During delivery hospitalisation, the mean length of stay for all PTL/PTB mothers was 6.0 days, and median costs were €2037. Length of stay and costs declined with increasing GA. Long term, PTL/PTB mothers' total median costs were €607 in Year 1, €332 in Year 2, and €388 in Year 3 post-delivery. In each year after delivery, median costs appeared to be greater for mothers who delivered at lower GAs. Conclusion In this description of costs and resource use among PTL/PTB mothers in Germany throughout the pregnancy and up to three years after delivery, the greatest costs were noted prior to delivery. Costs appeared to decrease with increasing GA, particularly during the delivery hospitalisation and the first year after delivery.